1983
DOI: 10.1007/bf02535425
|View full text |Cite
|
Sign up to set email alerts
|

Enzymatic hydrolysis of fractionated products from oils thermally oxidized in the laboratory

Abstract: Enzymatic hydrolysis of the acylglycerol products obtained from thermally oxidized vegetable oils was studied. Corn, sunflower and soybean oils were heated in the laboratory at 180 C for 50, 70 and 100 hr with aeration and directly fractionated by silicic acid column chromatography. By successive elution with 20%, then 60% isopropyl ether in n-hexane, and diethyl ether, the thermally oxidized oils were separated into three fractions: the nonpolar fraction (monomeric compounds), slightly polar fraction (dimeric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

1986
1986
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 25 publications
1
20
0
Order By: Relevance
“…In fact the polar fraction of the olive oil increased about 13 times after the heating treatment. This increase is agreement with previous data published in frying oil (21)(22)(23)(24)(25) and heated oils (19,26).…”
Section: Discussionsupporting
confidence: 95%
See 1 more Smart Citation
“…In fact the polar fraction of the olive oil increased about 13 times after the heating treatment. This increase is agreement with previous data published in frying oil (21)(22)(23)(24)(25) and heated oils (19,26).…”
Section: Discussionsupporting
confidence: 95%
“…According to Yoshida and Alexander (26), two typical groups of products-volatile breakdown derivatives and nonvolatile oxidation products-are produced by oil heating. The latter products include monomeric, dimeric, and polymeric compounds.…”
Section: Discussionmentioning
confidence: 99%
“…16,17 Nevertheless, the true digestibility of the heated sunflower oil (410 ± 34 g kg −1 ) found in the current study (Fig 1) tended to be higher than that found previously for heated olive oil (354 ± 68 g kg −1 ). 16 These data suggest that, although some compounds of the heated sunflower oil are resistant to pancreatic lipase or induce inhibition of enzyme lipases, 27,28 there are some compounds in this oil that improve the action of lipase in comparison with olive oil. Some time ago our group suggested that the in vitro digestion of palm olein and other oils improved when the surfactant concentration in the oil produced during frying increases.…”
Section: Discussionmentioning
confidence: 99%
“…Fractions I, 11,111 and IV consisted of acylglycerol monomers, dimers, trimers and polymers, respectively (Yoshida and Alexander 1983). The acylglycerol monomers decreased substantially with heating, and these values were compensated for by increases of more polar materials.…”
Section: Resultsmentioning
confidence: 98%